2022
DOI: 10.1590/1519-6984.244735
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the recombinant production and anticancer activity of thermostable L- asparaginase I from Pyrococcus abyssi

Abstract: L-Asparaginase catalysing the breakdown of L-Asparagine to L-Aspartate and ammonia is an enzyme of therapeutic importance in the treatment of cancer, especially the lymphomas and leukaemia. The present study describes the recombinant production, properties and anticancer potential of enzyme from a hyperthermophilic archaeon Pyrococcus abyssi. There are two genes coding for asparaginase in the genome of this organism. A 918 bp gene encoding 305 amino acids was PCR amplified and cloned in BL21 (DE3) strain of E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…In a report suggesting that Yarrowia lipolytica L-asparaginase inhibited the proliferation and growth of MOLT-4 and RAJI cells [57], the authors claimed that they investigated type II (secreted) L-asparaginase (K m not determined), but the sequence [58] indicated that the tested enzyme was an Ntn-hydrolase. In a report about anticancer properties of the Pyrococcus abyssi L-asparaginase [59], the authors described the enzyme as "L-asparaginase I". However, the provided K m value of 2.05 mM, sequence, and structure model unambiguously indicate a class 2 Ntn-hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…In a report suggesting that Yarrowia lipolytica L-asparaginase inhibited the proliferation and growth of MOLT-4 and RAJI cells [57], the authors claimed that they investigated type II (secreted) L-asparaginase (K m not determined), but the sequence [58] indicated that the tested enzyme was an Ntn-hydrolase. In a report about anticancer properties of the Pyrococcus abyssi L-asparaginase [59], the authors described the enzyme as "L-asparaginase I". However, the provided K m value of 2.05 mM, sequence, and structure model unambiguously indicate a class 2 Ntn-hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, it is difficult for enzymes of mesophilic origin to cover such a wide range of conditions required for their successful application in biotechnology, especially in the food industry. Extremophiles, in particular, thermophiles, which have been reported to produce L-ASNases with unique properties, can expand the number of biotechnologically available L-ASNases [9,[14][15][16][17]. According to experimental data, thermophilic L-ASNases (thermo-ASNases) can not only occupy a vacant niche of high-temperature food technologies but also compete with mesophilic enzymes in biomedicine [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As the main reason for the interruption of L-asparaginase treatment is the development of hypersensitivity, caused partly by the protein's high molecular weight and bacterial origin, an enzyme that leads to fewer side effects could be found in other microbial sources such as fungi, which are eukaryotic microorganisms evolutionarily closer to human beings in comparison to bacteria [15][16][17]. Furthermore, this biopharmaceutical of great pharmaceutical and industrial importance has an increasing demand in the international market that cannot be fulfilled by natural resources, thus bulk quantities of enzymes and proteins can be produced by recombinant DNA technology [18]. The heterologous expression of L-asparaginase from some microorganisms has already been reported in the literature .…”
Section: Introductionmentioning
confidence: 99%